Efficiency Effects of Premium-Setting Regimes under Workers' Compensation: Canada and the United States - Bruce, Christopher J.; Atkins, Frank J. (Journal of Labor Economics, 1993)
We develop a model in which it is predicted that more resources will be devoted to safety in a workers' compensation system with experience-rated premiums than in one with flat-rated premiums. We test this model by observing the effect on fatality rates of the move from flat rating to experience rating in the forestry and construction industries of Ontario, Canada. The evidence provides strong confirmation of the theory.